Editorial Note - Suphannachart, Waleerat (Asian Journal of Applied Economics, 2021)
This issue of Applied Economics Journal (AEJ) consists of six research papers and a review article covering a wide range of economic issues for both country groups and individual countries. The first paper applies both linear and non-linear approaches in determining the dynamic relationship between demography and direct taxes in OECD and non-OECD countries. The second paper investigates the impact of domestic borrowing together with FDI inflows and remittances on financial development of EU transition economies, using the cointegration and causality analysis. In the third paper, unit root tests with different approximations in modeling structural breaks are employed to investigate whether the ratio of military expenditures to GDP converged among NATO countries. The fourth paper uses the two-step generalized method of moments to empirically examine the effects of FDI, governance, and their interaction on income inequality for a panel of 37 developing countries. The fifth paper uses the autoregressive distributed lag (ARDL) and wavelet coherence techniques to reveal the validity of the environmental Kuznets curve (EKC) hypothesis in Indonesia. The sixth paper (written in Thai) applies behavioral economics frameworks to examine the effects of negative attitudes on Over-the-top (OTT) usage behavior in Thailand. The final article reviews empirical evidence on the optimal level of public spending in various countries confirming the existence of an inverted U-shaped relationship between government size and economic growth, known as the Armey curve.